[Ag(bpy)(PPhtBu2)(OCF3)]: a stable nucleophilic reagent for chemoselective and stereospecific trifluoromethoxylation of secondary alkyl nosylates. Issue 11 (24th April 2019) - Chen, Daoqian; Lu, Long; Shen, Qilong
Abstract : The development of a thermally stable and light-insensitive nucleophilic trifluoromethoxylative reagent [Ag(bpy)(PPh t Bu2 )(OCF3 )]2, which was synthesized in high yields via a three-step one-pot process from easily available trifluoromethyl triflate (TFMT) and AgF at room temperature, is described. Abstract : The development of a thermally stable and light-insensitive nucleophilic trifluoromethoxylative reagent [Ag(bpy)(PPh t Bu2 )(OCF3 )]2, which was synthesized in high yields via a three-step one-pot process from easily available trifluoromethyl triflate (TFMT) and AgF at room temperature, is described. The high reactivity of reagent2 was demonstrated by its high yielding chemoselective and stereospecific SN 2-type trifluoromethoxylation with secondary alkyl nosylates.